Shocking the system: AEDs in military resuscitation. Issue 4 (5th October 2017) - Buckley, Andrew M; Cox, A T; Rees, P
Abstract : Automated external defibrillator (AED) devices have been in routine clinical use since the early 1990s to deliver life-saving shocks to appropriate patients in non-clinical environments. As expectations of survival from out-of-hospital cardiac arrest increase, and evidence incontrovertibly points to reduced timelines as the most crucial factor in achieving return of spontaneous circulation, questions regarding the availability and location of AEDs in the UK military need to be readdressed. This article explores the background of AEDs and reviews their history, life-saving potential and defines current and best practice. It goes on to review the evidence surrounding training and looks to identify knowledge gaps that might be addressed effectively by future research. Finally, it makes recommendations regarding training, availability of AEDs on military bases and locations most likely to deliver good outcomes for military personnel in the future.